Iowa Birdline update, November 27, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for November 27, 1989. Highlights include the first Barn Owl sighting of the year and continued sightings of a California Gull. Epson - sheet feed/flatbed